COMPARISON BETWEEN TOTAL THYROIDECTOMY WITH LIGASURE SMALL JAW DEVICE VERSUS CONVENTIONAL VASCULAR LIGATURE TECHNIQUE - Waqas Ahmed (Army Medical College Rawalpindi, 2019)
Objective: To compare total thyroidectomy with LigaSure small jaw device with conventional vascular ligature technique in terms of mean operation time and intra-operative and postoperative blood loss.